Sex work stigma and non-disclosure to health care providers: data from a large RDS study among FSW in Brazil - Inês Dourado; Mark Drew Crosland Guimarães; Giseli Nogueira Damacena; Laio Magno; Paulo Roberto Borges de Souza Júnior; Celia Landmann Szwarcwald; The Brazilian FSW Group (BMC, 2019)
Abstract Background Stigma in health services may be detrimental to health seeking attitudes and practices. This study investigates non-disclosure of sex work to health care providers among female sex workers (FSW) in Brazil and its association with the utilization of health care services. Methods This study used cross-sectional respondent-driven sampling, carried out in 12 Brazilian cities to identify HIV risk behaviors among FSW. We first assessed statistical associations of sociodemographic, human right violations, health service access and utilization, and discrimination variables with non-disclosure of FSW status to health care providers as outcome. Secondly, we investigated the association of non-disclosure of FSW status with selected preventive health care outcomes: HIV testing, PAP smear exam, and post-exposure prophylaxis (PEP). Adjusted odds ratio with 95% confidence intervals were calculated by multivariable logistic regressions. Results Among 4245 recruited FSW, a high percentage received free condoms (82%) but only 24.4% were counseled on STI. Most FSW used non-specialized public healthcare routinely (62.6%), but only 51.5% had a Pap smear exam in the last two years and less than 40% were tested for HIV in the last 12 months. Among FSW who engaged in risky behavior (49.6%), only 8.3% used PEP. Regarding human rights violations, approximately 15% were required to give part of their earnings to owners of workplace establishments, 38% started sex work under 18 years old and 6% were required to periodically present their HIV test results. 21.3% reported having faced discrimination in health services, and 24.3% always disclosed their FSW status. Multivariable logistic models indicated significant associations of non-disclosure on the four healthcare outcomes, with lower odds of using preventive health services among women who did not disclose their sex work status, even after controlling for age, educational level, NGO affiliation, and type of health care routinely used. Conclusions Our results indicate that sex work stigmatization within health services may be one of the main barriers to STI control and HIV response among FSW. It is essential to combat stigmatization and discrimination against FSW in health services to guarantee the appropriate uptake of preventive services available in the public health system in Brazil.